Associations Between Serum Lycopene and Cancer-Related Fatigue: Findings From the US 2005–2006 National Health and Nutrition Examination Survey (NHANES). (7th June 2021) - Kleckner, Amber; Lin, Po-Ju; Gilmore, Nikesha; Kehoe, Lee; Dunne, Richard; Kleckner, Ian; Mustian, Karen; Jusko, Todd; van Wijngaarden, Edwin; Peppone, Luke
Abstract: Objectives: Cancer-related fatigue is characterized by an overwhelming sense of tiredness that cannot be relieved by sleep or rest; it often persists for years into survivorship. Maintaining appropriate nutritional status is critical during cancer treatment, though few studies have assessed relationships between diet quality and cancer-related fatigue. Herein, we aimed to investigate the association between serum lycopene, a proxy for diet quality, and fatigue in a large representative sample of the US population. Methods: Data were obtained from the 2005–2006 NHANES dataset. Serum total lycopene was quantified from fasting blood samples and used as a continuous variable. Patient-reported fatigue was assessed from a question on the validated Patient Health Questionnaire-9: "Over the last 2 weeks, how often have you been bothered by… feeling tired or having little energy?"; fatigue was categorized as no fatigue (0), low fatigue (1), or moderate-severe fatigue (2–3). Multinomial regression models were applied to assess the association between serum lycopene and fatigue while controlling for age, race/ethnicity, and body mass index. Results are reported as odds ratios (OR) and 95% confidence intervals (CIs) for having low or moderate-severe vs. no fatigue for a 10-μg/dL increase in serum lycopene for all participants and those with a previous cancer diagnosis. Results: Participants ( n  = 4091) were 48.3 ± 18.7 years old, 52% female, and 51.7% non-Hispanic White; 329 had a prior cancer diagnosis. A self-reported cancer diagnosis was associated with a 31.8% greater odds of having moderate-severe vs. no fatigue (OR = 1.32, 95% CI = 1.12–1.55) and a 6.8% greater odds of having low fatigue (OR = 1.07, 95% CI = 0.93–1.22). A 10-μg/dl increase in serum lycopene concentrations was associated with a 5.3% lower odds of moderate-severe vs. no fatigue (OR = 0.95, 95% CI = 0.90–0.99) and a similar odds of low fatigue (OR = 1.01, 95% CI = 0.97–1.04). These associations were similar for patients who had had a cancer diagnosis. Conclusions: Higher levels of serum lycopene were associated with lower odds of moderate-severe. Dietary interventions should be further explored for their associations with cancer-related fatigue among patients with cancer and cancer survivors. Funding Sources: National Cancer Institute.